Coping with Alcohol and Drug Problems: The Experiences of Family Members in Three Contrasting Cultures - Orford, Jim; Natera, Guillermina; Copello, Alex; Atkinson, Carol; Mora, Jazmin; Velleman, Richard; Crundall, Ian; Tiburcio, Marcela; Templeton, Lorna; Walley, Gwen (Routledge, 2005)
What difference does culture make? Coping with Alcohol and Drug Problems: The Experiences of Family Members in Three Contrasting Cultures aims to deepen and extend understanding of the experiences of family members trying to cope with the excessive drinking or drug taking of a relative. Comprehensive and thoroughly up to date, this book draws on the results of the cross-cultural study of alcohol and drug problems in the family, and places these results within the broader context of the international literature on the subject. By investigating the similarities and differences in the experiences of family members in three parts of the world, the authors reveal results which have far-reaching implications for professional intervention and prevention. Subjects covered include: models of understanding: how families continue to be pathologised and misunderstood. how family members cope. an integrated view of alcohol and drug problems in the family. ways of empowering family members. This book aims to demonstrate the possibility of a constructive alliance between professionals, substance misusing relatives, and the affected family members by thoroughly investigating the dilemmas that face family members and the lack of support they experience. This fascinating insight into the impact of alcohol and drug problems on family members will be a valuable resource for all those who are interested in substance misuse in family and cultural contexts, and particularly those who are interested in the treatment of alcohol and other drug problems.